تخييل الألوان في رواية اِعترافات اِمرأة لعائشة بنّور دراسة سيميو ثقافيّة - بوراس إبراهيم الخليل; عوادي يسمينة (University of Eloued جامعة الوادي, 2024)
تحاول هذه الدِّراسة الكشف عن ظاهرة التّخييل اللّوني في المقتطف السردي " وجع طفولي " من رواية "اعترافات امرأة" لعائشة بنور، وذلك من خلال الوقوف على أهم الانزياحات اللّونية ودلالاتها للوصول إلى أبرز السّمات والأنساق الثّقافية المدثّرة بين طيّات هذا الأثر الأدبي بالاعتماد على المنهج السّيميائي، والنّقد الثقافي، محاولين إيجاد إجابة للتّساؤلات التي وضعناها في مقدمة البحث و من جملة نتائج هذه الدّراسة : الصِّراع المخبوء بين درجات الألوان ومحاولة تمرد الأنا على الآخر لإثبات مركزيّة الأنثى المهمشة، بالإضافة إلى توظيف السّارد للأسود والأبيض كثنائية ضديّة تعكس طغيان النّسق الذّكوري على حساب النّسق الأنثويِّ في المترسِّب الجمعي ، الحمولة الدّلاليّة والنفسية للأسود والأبيض من خلال انزياحهما وخلخلة أصل مواضعهما للخروج بدلالات بكر. Abstract This study attempts to explore the phenomenon of color imagery in the narrative excerpt “Childish Pain” from the novel “Confessions of a Woman” by Aisha Bannour, by examining the most important color shifts and their connotations in order to reach the most prominent features and cultural patterns hidden within this literary work. Relying on the semiotic approach and cultural criticism, we will try to find an answer to the questions invoked in the introduction of the research. Among the results of this study: the hidden conflict among the nuances of colors and the attempt to rebel the ego against the other to prove the centrality of the marginalized female, in addition to the narrator’s use of black and white as an opposing duality that reflects the tyranny of the masculine pattern at the expense of the feminine pattern in the collective traditional sediment, the semantic and psychological load of black and white through their fine shifts and their displacement from the origin to produce virgin connotations.
مقال
Keywords: تخييل; لون; اعترافات امرأة; انزياح; سمة; نسق